Cognitive Recovery After Stroke: A Meta-analysis and Metaregression of Intervention and Cohort Studies. (July 2021) - Saa, Juan Pablo; Tse, Tamara; Baum, Carolyn M.; Cumming, Toby; Josman, Naomi; Rose, Miranda; O'Keefe, Sophie; Sewell, Katherine; Nguyen, Vinh; Carey, Leeanne M.
Background: Cognition affects poststroke recovery, but meta-analyses of cognition have not yet provided a comparison of observational and intervention evidence. Objective: To describe the trajectory of poststroke cognition and the factors that moderate it across intervention and observational cohorts. Methods: Six databases were searched up to January 2020. Studies describing quantitative changes in cognition in adults poststroke were included. Interventions were classified into pharmacological, therapist-led, nonroutine/alternative, and usual care. Summary estimates were compared via hierarchical mixed-effects models. Age, recovery stage, stroke etiology, cognitive domain targeted in studies, and intervention types were investigated as moderators of cognition. Recovery stage and intervention were further analyzed in a multiplicative metaregression model. Results: A total of 43 intervention trials and 79 observation cohorts involving 28 222 stroke participants were included. Heterogeneity was significant (τ 2 = 0.09; CI = 0.01-0.21, P < .001) with no evidence of publication bias. Cognitive recovery was greater in intervention trials ( g = 0.47; CI = 0.37-0.58) than observational cohorts ( g = 0.28; CI = 0.20-0.36) across all moderators analyzed. Nonroutine/alternative and pharmacological trials achieved the best overall results ( g = 0.57, CI = 0.42-0.73, and g = 0.52, CI = 0.30-0.74, respectively), followed by therapist-led ( g = 0.46; CI = 0.17-0.74), and usual care ( g = 0.28; CI = 0.11-0.45) interventions. Medium recovery effects (ie, g ≥ 0.5) were observed in examining first-ever stroke, executive function, visuo-perceptual, consciousness, and psychomotor skills, 61 to 180 days poststroke, in participants aged 65 to 70 years. Conclusion: Cognitive recovery is possible using different controlled interventions in all recovery stages, with smaller benefits ≥2 years poststroke. Longer-term studies are needed to determine the role of nonroutine/alternative therapies and the association between cognitive recovery and performance in everyday activities.